Enhancing Students’ Descriptive Text Writing Ability by Utilizing Indonesia Virtual Tour Website - Pratiwi, Ersa Andrea; Trisusana, Anis (JET ADI BUANA, 2024)
Writing is one of the essential language skills that students must learn and master. However, it is also considered the most difficult skill to acquire. Students encounter various challenges when composing written texts because there are many aspects to address in the writing process. For this reason, the teacher should be more creative and innovative in teaching writing to help students overcome those problems and enhance their writing ability. This study aims to investigate the use of Indonesia Virtual Tour website as visual media to improve students’ descriptive writing ability. A quantitative approach with a pre-experimental (One-Group Pretest-Posttest) design was employed. The subjects of this study were 33 seventh-grade students of a private junior high school in Surabaya. The sample was selected using purposive sampling. To collect data, the research instruments were pre-test and post-test on descriptive writing. The test results were subsequently analyzed using SPSS statistical software version 25. The findings demonstrated that using Indonesia Virtual Tour website in the descriptive learning process had positive impacts on students’ descriptive text writing abilities. This was indicated by the higher mean score of the post-test (81.12) compared to the pre-test (66.45). Furthermore, the result of the paired sample t-test showed that there was a significant difference in the students’ descriptive text writing ability before and after getting the treatment. In conclusion, utilizing Indonesia Virtual Tour website as visual media in the teaching and learning process effectively enhanced students’ writing ability in descriptive text.